KEPEMIMPINAN BARU DALAM SUKU DI MINANGKABAU (Studi : Masyarakat Nagari Simalidu Kecamatan Koto Salak Kabupaten Dharmasraya) - Sari, Putri Maya (Pendidikan Sosiologi, 2014)
Thesis Program Study Sociology at STKIP PGRI West Sumatera 2014. This research intent to describe about the new leadership in Minangkabauâs tribe in Nagari Simalidu, Kecamatan Koto salak, Kabupaten Dharmasraya. This research used Smelser theory about the social change. The kind of this research is qualitative research by using descriptive design.The result of this research are first, the factors that the causes of the establishing the new leadership on Minangkabauâs tribe in Nagari Simalidu, Kecamatan Koto Salak, Kabupaten Dharmasraya are 1) The conflict between mamak and nephew, 2) Conflict land disputes between mamak with mamak, 3)The leadership conflicts in the tribal. Secoud, the impact of the establishing the new leadership on Minangkabau tribeâs in Nagari Simalidu, Kecamatan Koto Salak, Kabupaten Dharmasraya: 1) The relationship between the same leaders is not good 2) the is relationship between the leader of the nephew, 3) The Restriction of involvement in community activities of societies.